A vaccine against Newcastle disease? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Newcastle disease has yet again struck down poultry in West Africa, in particular Senegal and Côte d Ivoire. Breeders who have vaccinated their flocks are very concerned with the high mortality rate being caused by this highly contagious disease,...